AB0988 Bone quality evaluation using the new trabecular bone score (TBS) tool in rheumatoid arthritis patients supplemented with vitamin d. (12th June 2018) - Casabella, A.; Paolino, S.; Ruaro, B.; Sulli, A.; Pizzorni, C.; Alessandri, E.; Fasciolo, D.; Seriolo, C.; Molfetta, L.; Odetti, P.; Seriolo, B.; Cutolo, M.
Abstract : Background: Patients affected by Rheumatoid Arthritis (RA) show an increased risk of low bone mass, as a result of multi-systemic disorders including toxic drug, low vitamin D levels, use of glucocorticoids and physical inactivity. Trabecular Bone Score (TBS), is an index extracted from the dual-energy X-ray absorptiometry (DXA) images, that provides an indirect measurement (Score) of bone axial microarchitecture and allows to get information about bone quality. 1, 2 Objectives: The aim of this investigation was to evaluate by TBS the bone quality in AR patients (high risk population) receiving vitamin D supplementation from at least 3 months (1000 IU/die). Methods: 108 female patients (mean age 61±8 years) affected by RA and 60 age- matched controls (CNT) (mean age 64±11 years) were analysed in winter time. Bone Mineral Density (BMD, g/cm 2 ) of the lumbar spine (L1-L4) was analysed using a DXA scan (GE, Lunar Prodigy). Lumbar spine TBS (TBS iNsight Medimaps) was derived for each spine DXA examination. All patients were evaluated for serum 25 hydroxyvitamin D (25(OH)D) serum concentrations. Results: RA patients showed lower 25(OH)D concentrations (18.4±1.3 ng/ml) than CNT (26.2±0.9 ng/ml; p<0.04) possibly due to low dosage and short treatment. Seventy-eight RA patients (80% of study population) presented a bone loss that was significant when compared to the control group (p<0.001). In particular, BMD was found significantly lower in RA patients compared with matched control group (respectively, Lumbar spine: 0.862±0.194 g/cm 2 vs 1.240±0.932 g/cm 2 ;Femoral neck: 0.668±0.141 g/cm 2 vs 0.845±0.164 g/cm 2 ; Ward: 0.486±0.221 g/cm 2 vs 0.657±0.106 g/cm 2 ; Trochanter: 0.598±0.231 g/cm 2 vs 0.725±0.143 g/cm 2 ; Total hip: 0.764±0.244 g/cm 2 vs 1.033±0.161 g/cm 2, all p<0.001). Likewise, lumbar spine TBS score was found significantly lower in RA patients when compared with CNT (0.904±0.148 vs 1.361±0.126, both p<0.001) Conclusions: This study shows in RA patients a reduction of TBS values that seem placed side by side with reduced BMD values and in presence of serum 25(OH)D insufficiency. A more carefull analysis of the clinical status/treatments should let to better identify RA patients at higher risk of bone loss. Reference: [1] . Cutolo M et al. Autoimmun Rev 2011:12;84–7, 2. Avouac J, et al. Arthritis Care Res 2012;64:1871–8 Disclosure of Interest: None declared